1992
DOI: 10.1182/blood.v80.4.960.960
|View full text |Cite
|
Sign up to set email alerts
|

Sustained antithrombotic activity of hirudin after its plasma clearance: comparison with heparin

Abstract: Thrombus extension in patients with venous thromboembolism is due to the accretion of fibrin onto existing thrombi. Extension is promoted by both circulating and thrombus-bound thrombin, which convert fibrinogen to fibrin. Heparin is an effective antithrombotic agent, but it requires continuous administration to achieve persistent inhibition of thrombus extension. Heparin is highly effective in inhibiting fluid phase thrombin, but is a relatively ineffective inhibitor of thrombus- bound thrombin. Hirudin, unli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(27 citation statements)
references
References 12 publications
2
25
0
Order By: Relevance
“…52,53 Surprisingly, the inhibition continued beyond the time at which hirudin would have been removed from the circulation through excretion, and is therefore due to either an alteration to the amount of thrombin bound to the clot or the hirudin itself binding to and inhibiting any thrombin actually within in the clot. 54…”
Section: Venous Thrombosismentioning
confidence: 99%
“…52,53 Surprisingly, the inhibition continued beyond the time at which hirudin would have been removed from the circulation through excretion, and is therefore due to either an alteration to the amount of thrombin bound to the clot or the hirudin itself binding to and inhibiting any thrombin actually within in the clot. 54…”
Section: Venous Thrombosismentioning
confidence: 99%
“…The antithrombotic action of hirudin persist beyond its biological activity. [2] Internal infestation through natural orifices may require medical intervention. [3] There is a single case report of altered coagulation profile due to leech bite requiring fresh frozen plasma.…”
Section: Case Reportmentioning
confidence: 99%
“…2 Interestingly, thrombin inhibition was sustained beyond the time at which r-hirudin was removed from the circulation. 11 Other experimental studies demonstrated that after either intravenous or subcutaneous administration, hirudin produced a dose-related inhibition of thrombus weight. The activated partial thromboplastin time (aPTT) required to inhibit thrombus formation was lower with hirudin than it was with heparin in different models.…”
Section: Antithrombotic Activity Of Hirudin In Experimental Studiesmentioning
confidence: 99%
“…The efficacy of r-hirudin in preventing venous and arterial thrombosis was demonstrated in different animal models of disseminated intravascular coagulation (DIC) induced by infusion of active clotting factors or endotoxin, venous thrombosis induced by stasis, and arterial thrombosis induced by vessel wall lesions. [7][8][9][10][11] Doses of 0.03 to 1 mg/kg were effective in DIC and in venous thrombosis, whereas 1 to 4 mg/kg were needed in arterial models. Thus, stasis-induced venous thrombosis and disseminated microthrombosis were most sensitive, whereas comparatively higher doses were required in arterial thrombosis, possibly because inhibition of the thrombin-platelet plug requires higher concentrations than does the inhibition of the thrombin-fibrinogen reaction.…”
Section: Antithrombotic Activity Of Hirudin In Experimental Studiesmentioning
confidence: 99%